Device considerations for development of conductance-based biosensors - Lee, Kangho (American Institute of Physics, 2009)
Design and fabrication of electronic biosensors based on field-effect-transistor (FET) devices require understanding of interactions between semiconductor surfaces and organic biomolecules. From this perspective, we review practical considerations for electronic biosensors with emphasis on molecular passivation effects on FET device characteristics upon immobilization of organic molecules and an electrostatic model for FET-based biosensors.